Simultaneous Synthesis and Sintering of a Nanostructured MgTiO3-MgTi2O5-MgAl2O4 Composite by Pulsed Current Heating and its Mechanical Properties - Du, Song-Lee; Doh, Jung-Mann; Yoon, Jin Kook; Shon, In-Jin (KOREAN INST METALS MATERIALS, 2013)
Nanocrystalline materials have received much attention as advanced engineering materials with improved physical and mechanical properties. As nanomaterials possess high strength, high hardness, excellent ductility and toughness, undoubtedly, more attention has been paid for the application of nanomaterials. Nanopowders of Al2O3, MgO and TiO2 were made by high energy ball milling. The simultaneous synthesis and sintering of a nanostructured MgTiO3-MgTi2O5-MgAl2O4 composite was investigated by the pulsed current heated sintering process. A highly dense nanostructured MgTiO3-MgTi2O5-MgAl2O4 composite was produced with simultaneous application of 80 MPa pressure and pulsed current within one min. The sintering behavior, gain size and mechanical properties of MgTiO3-MgTi2O5-MgAl2O4 composite were investigated.